2022
DOI: 10.1017/fms.2022.16
|View full text |Cite
|
Sign up to set email alerts
|

Polish spaces of Banach spaces

Abstract: We present and thoroughly study natural Polish spaces of separable Banach spaces. These spaces are defined as spaces of norms, respectively pseudonorms, on the countable infinite-dimensional rational vector space. We provide an exhaustive comparison of these spaces with admissible topologies recently introduced by Godefroy and Saint-Raymond and show that Borel complexities differ little with respect to these two topological approaches. We investigate generic properties in these spaces and compare them with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…In [14] we compared our spaces P ∞ and B with (SB, τ ). In particular, we observed that whenever τ is an admissible topology, then there exists a continuous map Φ : (SB, τ ) → P such that for every F ∈ SB(X) we have F ≡ X Φ(F ) isometrically, see [14,Theorem 3.3]. Thus, from our results obtained in the coding P ∞ one may easily deduce also results formulated in the language of admissible typologies.…”
Section: Notions and Results Frommentioning
confidence: 99%
See 4 more Smart Citations
“…In [14] we compared our spaces P ∞ and B with (SB, τ ). In particular, we observed that whenever τ is an admissible topology, then there exists a continuous map Φ : (SB, τ ) → P such that for every F ∈ SB(X) we have F ≡ X Φ(F ) isometrically, see [14,Theorem 3.3]. Thus, from our results obtained in the coding P ∞ one may easily deduce also results formulated in the language of admissible typologies.…”
Section: Notions and Results Frommentioning
confidence: 99%
“…Finally, in order to avoid any confusion, we emphasize that if we write that a mapping is an "isometry" or an "isomorphism", we do not mean it is surjective if this is not explicitly mentioned. [14]. The most important notion we want to recall is the Polish spaces of Banach spaces.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations